Observations of binary stars with the differential speckle survey instrument. VI. Measures during 2014 at the Discovery Channel Telescope - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W.; Ciastko, Lindsay A.; Everett, Mark E.; Bjorkman, Karen S. (The Astronomical Journal, 2015)
We present the results of 938 speckle measures of double stars and suspected double stars drawn mainly from the Hipparcos Catalog, as well as 208 observations where no companion was noted. One hundred fourteen pairs have been resolved for the first time. The data were obtained during four observing runs in 2014 using the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope. The measurement precision obtained when comparing to ephemeris positions of binaries with very well-known orbits is generally less than 2 mas in separation and 0.°5 in position angle. Differential photometry is found to have internal precision of approximately 0.1 mag and to be in very good agreement with Hipparcos measures in cases where the comparison is most relevant. We also estimate the detection limit in the cases where no companion was found. Visual orbital elements are derived for six systems. © 2015. The American Astronomical Society. All rights reserved.
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: interferometric; techniques: photometric

High-resolution multi-band imaging for validation and characterization of small kepler planets - Everett, Mark E.; Barclay, Thomas; Ciardi, David R.; Horch, Elliott P.; Howell, Steve B.; Crepp, Justin R.; Silva, David R. (The Astronomical Journal, 2015)
High-resolution ground-based optical speckle and near-infrared adaptive optics images are taken to search for stars in close angular proximity to host stars of candidate planets identi fied by the NASA Kepler Mission. Neighboring stars are a potential source of false positive signals. These stars also blend into Kepler light curves, affecting estimated planet properties, and are important for an understanding of planets in multiple star systems. Deep images with high angular resolution help to validate candidate planets by excluding potential background eclipsing binaries as the source of the transit signals. A study of 18 Kepler Object of Interest stars hosting a total of 28 candidate and validated planets is presented. Validation levels are determined for 18 planets against the likelihood of a false positive from a background eclipsing binary. Most of these are validated at the 99% level or higher, including five newly validated planets in two systems: Kepler-430 and Kepler-431. The stellar properties of the candidate host stars are determined by supplementing existing literature values with new spectroscopic characterizations. Close neighbors of seven of these stars are examined using multi-wavelength photometry to determine their nature and influence on the candidate planet properties. Most of the close neighbors appear to be gravitationally bound secondaries, while a few are best explained as closely co-aligned field stars. Revised planet properties are derived for each candidate and validated planet, including cases where the close neighbors are the potential host stars. © 2015. The American Astronomical Society. All rights reserved.
Keywords: Binaries: visual; Planetary systems; Planets and satellites: detection; Planets and satellites: fundamental parameters; Surveys; Techniques: high angular resolution; dept.phy; peer-reviewed

Observations of binary stars with the differential speckle survey instrument. V. toward an empirical metal-poor mass–luminosity relation - Horch, Elliott P; Altena, William F Van; Demarque, Pierre; Howell, Steve B; Everett, Mark E; Ciardi, David R; Teske, Johanna K; Henry, Todd J; Winters, Jennifer G (The Astronomical Journal, 2015)
In an effort to better understand the details of the stellar structure and evolution of metal-poor stars, the Gemini North telescope was used on two occasions to take speckle imaging data of a sample of known spectroscopic binary stars and other nearby stars in order to search for and resolve close companions. The observations were obtained using the Differential Speckle Survey Instrument, which takes data in two filters simultaneously. The results presented here are of 90 observations of 23 systems in which one or more companions was detected, and six stars where no companion was detected to the limit of the camera capabilities at Gemini. In the case of the binary and multiple stars, these results are then further analyzed to make first orbit determinations in five cases, and orbit refinements in four other cases. The mass information is derived, and since the systems span a range in metallicity, a study is presented that compares our results with the expected trend in total mass as derived from the most recent Yale isochrones as a function of metal abundance. These data suggest that metal-poor main-sequence stars are less massive at a given color than their solar-metallicity analogues in a manner consistent with that predicted from the theory. © 2015. The American Astronomical Society. All rights reserved..
Keywords: astrometry; binaries: visual; dept.phy; peer-reviewed; techniques: high angular resolution; techniques: interferometric; techniques: photometric

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438), KOI-4742 (Kepler-442)); techniques: photometric

A seismic and gravitationally bound double star observed by Kepler - Appourchaux, T; Antia, H M; Ball, Warrick H; Creevey, O; Lebreton, Y; Verma, Kuldeep; Vorontsov, Sergei V; Campante, T L; Campante, T L; Davies, G R; Davies, G R; Gaulme, Patrick; et al. (Astronomy and Astrophysics, 2015)
Context. Solar-like oscillations have been observed by Kepler and CoRoT in many solar-type stars, thereby providing a way to probe stars using asteroseismology. Aims. The derivation of stellar parameters has usually been done with single stars. The aim of the paper is to derive the stellar parameters of a double-star system (HIP93511), for which an interferometric orbit has been observed along with asteroseismic measurements. Methods. We used a time series of nearly two years of data for the double star to detect the two oscillation-mode envelopes that appear in the power spectrum. Using a new scaling relation based on luminosity, we derived the radius and mass of each star. We derived the age of each star using two proxies: one based upon the large frequency separation and a new one based upon the small frequency separation. Using stellar modelling, the mode frequencies allowed us to derive the radius, the mass, and the age of each component. In addition, speckle interferometry performed since 2006 has enabled us to recover the orbit of the system and the total mass of the system. Results. From the determination of the orbit, the total mass of the system is 2.34-0.33 +0.45 M⊙. The total seismic mass using scaling relations is 2.47 ± 0.07 M⊙. The seismic age derived using the new proxy based upon the small frequency separation is 3.5 ± 0.3 Gyr. Based on stellar modelling, the mean common age of the system is 2.7-3.9 Gyr. The mean total seismic mass of the system is 2.34-2.53 M⊙ consistent with what we determined independently with the orbit. The stellar models provide the mean radius, mass, and age of the stars as RA = 1.82-1.87R⊙, MA = 1.25-1.39 M⊙, AgeA = 2.6-3.5 Gyr; RB = 1.22-1.25 R⊙, MB = 1.08-1.14 M⊙, AgeB = 3.35-4.21 Gyr. The models provide two sets of values for Star A: [1.25-1.27] M⊙ and [1.34-1.39] M⊙. We detect a convective core in Star A, while Star B does not have any. For the metallicity of the binary system of Z ≈ 0.02, we set the limit between stars having a convective core in the range [1.14-1.25] M⊙. © ESO, 2015.
Keywords: Asteroseismology; Binaries: general; Interferometry; Orbits; Seismology; Separation; Speckle; Stars; Stars: evolution; Stars: solar types; asteroseismology; astrometry; binaries: general; dept.phy; stars: evolution; stars: solar-type